Parents' Perception of Offline Schools During the Covid-19 Pandemic - Ikhsan, Yasmin Karimah; Maulida, Nur Rachmawati; Azzahra, Zumara Ma'rifah; Wijayanti, Sri (Journal of Community Medicine and Public Health Research, 2022)
When Covid-19 began to enter Indonesia, the entire school process was immediately switched to an online method. Various efforts have been made by parents to deal with online schools, which unwittingly affect their mental condition, which so far has never accompanied children to learn from home. Therefore, the Indonesian government continues to strive to improve the quality of education during the pandemic. This study aimed to determine parents' perceptions of offline schools during the Covid-19 pandemic. The method used was descriptive with a questionnaire given to 67 mothers. The results were that most mothers (88.1%) felt that online learning reduced children's learning capacity. Most mothers (25.7%) complained that the absorption of material was less effective and maximal, 65.7% of mothers felt that offline learning should be implemented immediately because direct interaction with teachers was considered more comprehensive and effective, and 70.1% of mothers allowed their children to study offline during the pandemic with strict health protocols. Almost all respondents (97%) stated that offline schools can develop children potentially better than online schools. Most mothers (70.1%) felt that their children can maintain health protocols while at school if they are allowed to go to school offline.